Advances in stem cell‐based regenerative medicine: Despite setbacks and failures, therapies to replace damaged tissue are making their way into the clinic. (8th April 2019) - Hunter, Philip
Abstract : Although stem cell‐based regenerative medicine has been haunted by scandals and setbacks, scientists have been persistently making progress towards clinical applications and new therapies.